Acidity control of a Typic Distrudept, under no-tillage, after surface application of micronized liming materials: yield and soil reaction. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
We measured the relative yield (RY), relative yield change (RYG) and production efficiency (PE) of wheat, soybean, black oat and maize, during the years 2012 to 2016; and also evaluate the effect after 5, 11, 23, 34 and 45 months of the surface application of dose of liming materials (LM), in various soil layers (0-5, 5-10, 10-20, 20-40 and 40-60 cm) of a Typic Distrupedt, of attributes: active acidity (pH), soil base saturation (V), exchangeable calcium (Ca), magnesium (Mg) and potassium (K), the percentage (%) of Ca and Mg in the cation exchange capacity at pH 7.0 (CEC) and cationic relationship (CR) as Ca/Mg and (Ca+Mg)/K. The experimental design used was completely randomized blocks in split-plot with four replications. In the plots were studied the dolomitic limestone (DL) and the micronized liming material (MLM): granulated micronized calcite (GMC) and dolomite (GMD) and carbonated suspension (CS). In the subplots were studied three doses of each the LM aiming to increase V to 50, 70 and 90 %, besides of control treatment. The MLM presented major RY and PE along the time than DL. Besides, the major RYG of MLM major residual effect and major/maintenance crops yield. If we consider only PE, better results are found in the dose aiming V to 61 % for all the LM, showing that it is the adequate V for acidity control of a Typic Distrudept. Despite the MLM are more fineness than DL, the effectiveness for control soil acidity in subsoil were inefficient. However, the MLM present lower gap between the V estimated and obtained, manly in the 0-5 cm layer than DL. LM in the V to 50-70 % increased Ca, Mg and K, in 0-5 cm layer, up to 34 months after application. In the 0-20 cm layer, the better CR occurred at 11 months after application. The K increased as it decreased the % of Mg in the CEC.
Keywords: reação do solo; solo com carga variável; saturação por bases do solo; disponibilidade de nutrientes; rendimento das culturas; soil reaction; soil with variable charge; soil base saturation; nutrient available; crops yield; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA